The impact of small-sided games on cognitive fatigue and decision-making ability of elite youth soccer players - Mitrotasios, M.; Christofilakis, O.; Armatas, V.; Apostolidis, N. (Facta Universitatis: Series Physical Education and Sport, 2021)
Fatigue is highly correlated to performance decline. Extensive periods of cognitive and physical demands induce cognitive and physiological fatigue respectively. The purpose of the present study was to investigate the impact of the number of small-sided games (SSG) on physical loading, cognitive fatigue, and decision-making ability on the ball action of youth elite soccer players. Ten U20 players were enrolled in the study and performed six 4vs4 plus 2 GK SSGs. Physiological loading was measured from blood lactate and heart rate, for cognitive fatigue players provided subjective ratings (VAS), while the decision-making ability was evaluated through video recordings in 3 phases. The results showed that the SSGs induced high mean values for physiological loadings, and reported statistically significant fatigue after the 3rd game, based on the questions "Cognitive Fatigue" and "Cognitive Effort". Regarding the decision-making ability, players demonstrated 59.8% positive decisions in Phase A of the actions, 86.5% in Phase B, and 55.1% in Phase C with no statistical significance between games. The comparison between games 1-3 and 4-6 indicated significantly greater motor outcome effectiveness for the first group of games (63.5%). The results indicated that the number of intense SSGs in training should be selected wisely, in order to contribute to improving the quality and the effectiveness of the decision-making ability of the soccer players under the pressure of time, space, and opponents in the match.